Imitating model for electromagnetic process research in traction networks of the direct current - Сиченко, Віктор Григорович (Eastern-European Journal of Enterprise Technologies, 2012)
Consider methodologies for constructing a simulation model for the study of electromagnetic processes electrified section of DC